Research on the acceptance of ICT among university students in Hong Kong—an empirical analysis based on the extended innovation diffusion theory - Mei, Shuhua; Atmadja, Anantawikrama Tungga; Artini, Luh Putu; Rahmawati, Putu Indah (Frontiers in Education, 2025)
The integration of digital technology into higher education is reshaping academic practices, particularly in Hong Kong’s multicultural post-secondary institutions. This study applies an extended Innovation Diffusion Theory (IDT)—incorporating cultural compatibility and institutional mandates as contextual extensions to the classic framework—to examine ICT acceptance among 386 undergraduates from two local institutions. Findings indicate that relative advantage and observability significantly drive adoption, while complexity (e.g., English-only interfaces) hinders it. Institutional mandates (e.g., Canvas usage) positively influence late majority learners, and cultural differences affect adoption—non-local students prefer bilingual tools. Adopter categories are identified: innovators (11.7%, mostly design/IT majors) actively use AI tools, while laggards (5.2%) face barriers like outdated devices. Recommendations include localized Chinese guides, device subsidies, and scenario-based demonstrations. Limitations include a narrow sample, suggesting future expansion to more institutions.